2011
DOI: 10.1159/000328269
|View full text |Cite
|
Sign up to set email alerts
|

Tattoo Removal

Abstract: Over 50,000 new tattoos are placed each year in the United States. Studies estimate that 24% of American college students have tattoos and 10% of male American adults have a tattoo. The rising popularity of tattoos has spurred a corresponding increase in tattoo removal. Not all tattoos are placed intentionally or for aesthetic reasons though. Traumatic tattoos due to unintentional penetration of exogenous pigments can also occur, as well as the placement of medical tattoos to mark treatment boundaries, for exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…Not all tattoos are placed intentionally; penetration of exogenous pigments can occur from road dirt from an accident, graphite in pencils, or gunpowder, and many people may want these unintentional tattoos removed. 44 Adolescents may overestimate the effectiveness of tattoo removal when having one placed and should be instructed that tattoo placement is permanent, and it is expensive and sometimes difficult to remove them. 3 Tattoo removal techniques can be categorized as mechanical, chemical, ablative, and selective.…”
Section: Tattoo Removalmentioning
confidence: 99%
See 3 more Smart Citations
“…Not all tattoos are placed intentionally; penetration of exogenous pigments can occur from road dirt from an accident, graphite in pencils, or gunpowder, and many people may want these unintentional tattoos removed. 44 Adolescents may overestimate the effectiveness of tattoo removal when having one placed and should be instructed that tattoo placement is permanent, and it is expensive and sometimes difficult to remove them. 3 Tattoo removal techniques can be categorized as mechanical, chemical, ablative, and selective.…”
Section: Tattoo Removalmentioning
confidence: 99%
“…3 Tattoo removal techniques can be categorized as mechanical, chemical, ablative, and selective. 44 "Q-switched" lasers are the current state-of-the-art tattoo removal method. The laser wavelength is adjusted to match the absorption pattern of the different color pigments.…”
Section: Tattoo Removalmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review and meta-analysis of tattooing and risk of Original reported rates of HCV infection were transformed as follows: 43 Ten to 16% of youth (12−18 years old) and 3%−10% of the general population reported having permanent tattoos, 44 and an estimated 50 000 new tattoos are being done every year in the US. 45 In Canada, 10%−12% of Enhanced Street Youth Surveillance respondents reported having a tattoo (Surveillance and Epidemiology Division, Centre for Communicable Diseases and Infection Control, Public Health Agency of Canada, unpublished data, 2012). Although it has a low probability of transmission, sexual transmission of HCV infection has been documented in people who have multiple sexual partners 46 and who are co-infected with sexually transmitted infections.…”
Section: 39mentioning
confidence: 99%